Altered sleep during spontaneous cannabinoid withdrawal in male mice. Issue 2 (10th March 2022) - Missig, Galen; Mehta, Niyati; Robbins, James O.; Good, Cameron H.; Iliopoulos-Tsoutsouvas, Christos; Makriyannis, Alex; Nikas, Spyros P.; Bergman, Jack; Carlezon, William A.; Paronis, Carol A.
Abstract : Cessation of cannabinoid use in humans often leads to a withdrawal state that includes sleep disruption. Despite important health implications, little is known about how cannabinoid abstention affects sleep architecture, in part because spontaneous cannabinoid withdrawal is difficult to model in animals. In concurrent work we report that repeated administration of the high-efficacy cannabinoid 1 (CB1) receptor agonist AM2389 to mice for 5 days led to heightened locomotor activity and paw tremor following treatment discontinuation, potentially indicative of spontaneous cannabinoid withdrawal. Here, we performed parallel studies to examine effects on sleep. Using implantable electroencephalography (EEG) and electromyography (EMG) telemetry we examined sleep and neurophysiological measures before, during, and after 5 days of twice-daily AM2389 injections. We report that AM2389 produces decreases in locomotor activity that wane with repeated treatment, whereas discontinuation produces rebound increases in activity that persist for several days. Likewise, AM2389 initially produces profound increases in slow-wave sleep (SWS) and decreases in rapid eye movement (REM) sleep, as well as consolidation of sleep. By the third AM2389 treatment, this pattern transitions to decreases in SWS and total time sleeping. This pattern persists following AM2389 discontinuation and is accompanied by emergence of sleep fragmentation. Double-labeling immunohistochemistry for hypocretin/orexin (a sleep-regulating peptide) and c-Fos (a neuronal activity marker) in lateral hypothalamus revealed decreases in c-Fos/orexin+ cells following acute AM2389 and increases following discontinuation, aligning with the sleep changes. These findings indicate that AM2389 profoundly alters sleep in mice and suggest that sleep disruption following treatment cessation reflects spontaneous cannabinoid withdrawal.